A New Species of Creptotrematina (Trematoda: Allocreadiidae) from the Red Minor Tetra, Hyphessobrycon eques (Steindachner, 1882) (Characidae) from Brazil, with Comments on the Genetic Divergence of C. Aguirrepequenoi Jiménez-Guzmán, 1973 across a Wide Geographical Range in Middle America - Ebert, Mariana Bertholdi [UNESP]; Hernández-Mena, David I.; de León, Gerardo Pérez-Ponce; da Silva, Reinaldo José [UNESP] (Springer Nature, 2024)
Background: Allocreadiids are relatively small digeneans that appear to be restricted to freshwater systems distributed across the world. Allocreadiids are highly diverse in the Americas, particularly in the Neotropical biogeographical region. Their taxonomic history has been rather controversial, with several taxonomic reassessments and the description of new genera and species. Methods: We sampled Creptotrematina specimens from a characid collected in the Pardo River, Paranapanema River basin in Brazil, and specimens of C. aguirrepequenoi, from Astyanax spp. in several localities between northern Mexico and Costa Rica. The specimens were studied through integrative approaches using morphological and molecular analyses of the 28S rDNA gene and two different regions of the COI mtDNA gene. Results: We describe a new species of Creptotrematina which is differentiated from other congeners by the overall body size, but in particular by the size and position of the cirrus-sac, distribution of the vitelline follicles, and extension of uterine loops in the posterior end of body. Phylogenetic analyses of the 28S rDNA and COI mtDNA genes placed the new species in a monophyletic clade together with all other sequenced species of Creptotrematina, and as a sister species of C. batalhensis. Genetic divergences between the new species and other Creptotrematina spp. varied from 1.1 to 1.2% for the 28S rDNA and 12.4–14.3% for the COI mtDNA. Phylogenetic analysis based on COI mtDNA showed the isolates of C. aguirrepequenoi grouped in four monophyletic clades representing populations geographically separated along a wide geographical range spanning between northern Mexico and Costa Rica, with an estimated genetic divergence between 3.9% and 8.9%. Conclusions: Our findings based on integrative analyses recognize Creptotrematina saltograndensis n. sp. from a characid collected in the Pardo River, Paranapanema River basin in Brazil and provide validation of the wide geographical distribution of C. aguirrepequenoi across Middle-America parasitizing Astyanax spp.; the genetic divergence of the species through the analysis of two regions of COI mtDNA points towards considering it represent a species complex, although we refrain at the moment on describing a new species, awaiting for further verification using other molecular markers, and obtaining fresh material for a more detailed taxonomic analyses. This study increases the known diversity of allocreadiids and contributes to the understanding of evolutionary relationships, host-parasite relationships, and biogeographic history of the group.
Keywords: 28S rDNA; COI mtDNA; Digenea; Freshwater fishes; Neotropical region